STUDI TENTANG MONUMEN ORANG RANTAI DI KOTA SAWAHLUNTO - Rikki Alexander, Dra. Lisa Wisdiarti, M.Sn., Drs. Erfahmi, M.Sn. (Universitas Negeri Padang, 2017)
The purpose of this research is to know the form, function, and meaning found on People Chain Monument in Sawahlunto City. This research includes the type of qualitative research with descriptive approach and date collected in the form of the results of interviews, interview, images and not the numbers.The findings of this study, diantaranta are: 1) the form of the monument of this chain people are divided into two namely the top form, and the bottom form. 2) The monument of a chain man serves as a reminiscent of Mbah Suro and the chain person. 3) the monument of the chains has the meaning of struggle and proves the identity of the city of Sawhlunto as a mine tour city.Kata Kunci: Monumen, Bentuk, Fungsi, dan Makna